Drotaverine induced urticaria: a case report - Babu, Harry; Asia, Anand J.; Sontakke, Smita D.; Bachewar, N. P. (International Journal of Basic & Clinical Pharmacology, 2025)
Drotaverine belongs to the hydroisoquinolone class of drugs. It is an effective antispasmodic drug used in the symptomatic treatment of various conditions such as GI diseases, biliary dyskinesia and smooth muscle spasms. There are a very few hypersensitivity reactions reported with this drug. Drotaverine induced cutaneous lesions is a very rare adverse effect and one such occurrence is discussed here. Diagnosis is a clinical one, made usually on the basis of knowledge obtained by medical history and physical examination.